The Effect Of Variation Milliampere-Seconds (mAs) To Entrance Skin Exposure And Radiographic Anatomy Image In Examination of Columna Vertebra Lumbal With Ap Projection - Siti Daryati; Gatot Murti Wibowo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
Quantitative Descriptive research with experimental opproach was done with x-ray machiine type UD150l-30E. The data of experiment was taken with made eight radiographs and the ESE measurement is conducted using TLD which layed on surface of abdomen phantom or at central point. Exposure was taken with eight times with eight variation of mAs. It is about 8,10,12,14,16,18,20 and 22 mAs with 80 kV. The result shown that there is a effetct of variation mAs to ESE and quality of radiographic anatomy image. Higher mAs result higher ESE and increase mAs about two interval reslut average value is 142 mR. Variation of mAs result variation of image quality. A good image quality with 19,1 cm part thickness resulted with use 18 mAs and 20 mAs with 80 kV. Optimum mAs with 80 kV in this research’s is 18 mAs.